TO REACH THE UNREACHED PEOPLE: MENGKAJI MISI DAN PELAYANAN MATHEUS MANGENTANG - Adi Putra (Phronesis: Jurnal Teologi dan Misi, 2023)
One of Indonesia's most critical mission figures is Matheus Mangentang (MM). His project was carried out across nearly all of Indonesia through SETIA and GKSI. Nevertheless, there is a paucity of literature and studies analyzing the missions that MM has completed. Researchers discovered numerous findings through qualitative approaches, particularly literature or literature studies. First, MM's compassion for oppressed souls—the bulk of whom lived in isolated or rural areas—was the catalyst for the birth of his mission. Therefore, that inspired him to reach out to them, uplift them, and share the good news of redemption with them to ultimately free them from spiritual, educational, and even economic weakness.